2017
DOI: 10.1007/s00508-017-1174-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of hantavirus infections in Bulgaria

Abstract: The present report describes for the first time comparative analysis of epidemiological features, clinical manifestations and laboratory findings of DOBV and PUUV infections in Bulgaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
2
0
4
Order By: Relevance
“…Abnormal laboratory test results returned to normal within approximately 3-5 days, with a range of 1-13 days. These findings seem to be similar to those of other reported patients infected with PUUV (Christova et al, 2017;Golovljova et al, 2007;Latus et al, 2015;Skarphedinsson, Thiesson, Shakar, & Tepel, 2015;Vilibic-Cavlek et al, 2017).…”
Section: çElebisupporting
confidence: 92%
“…Abnormal laboratory test results returned to normal within approximately 3-5 days, with a range of 1-13 days. These findings seem to be similar to those of other reported patients infected with PUUV (Christova et al, 2017;Golovljova et al, 2007;Latus et al, 2015;Skarphedinsson, Thiesson, Shakar, & Tepel, 2015;Vilibic-Cavlek et al, 2017).…”
Section: çElebisupporting
confidence: 92%
“…Surprisingly, past PUUV infection was detected more often than DOBV in this study: PUUV seroprevalence rate was calculated as 2.3% versus 0.8% of DOBV. Recent study of clinically manifested hantavirus infections in Bulgaria revealed that infections in 16/23 (69.6%) patients with HFRS recognized for 2 years, 2013‐2014, were caused by DOBV while PUUV was shown as prevalent in Slovenia, Croatia, Bosnia, and Herzegovina .…”
Section: Discussionmentioning
confidence: 99%
“…Secara umum, patogenesis Hantavirus melibatkan proses multifaktorial yang kompleks, termasuk strain virus, kontribusi respon imun, disfungsi keping darah, dan deregulasi fungsi sel barier endotelial atau predisposisi genetik terkait tipe Human Leucocyte Antigen, yang berpengaruh pada keparahan penyakit. Sebagai contoh infeksi virus Dobrava-Belgrade (DOBV) menyebabkan penyakit yang lebih parah dibanding Puumala virus (PUUV) (Christova et al 2017;Zupanc et al 2019).…”
Section: Mekanisme Penularanunclassified
“…Secara umum, Hantavirus menyebabkan dua penyakit yang berbeda pada manusia, yaitu Hantavirus Pulmonary Syndrome (HPS) atau Hantavirus Cardiopulmonary Syndrome (HCPS), serta Hemorrhagic Fever with Renal Syndrome (HFRS) (Christova et al 2017). Hantavirus menyebabkan infeksi meluas pada manusia yang melibatkan pembuluh darah perifer dan sangat mempengaruhi permeabilitasnya (Maes et al 2009).…”
Section: Manifestasi Penyakit Hantavirusunclassified
See 1 more Smart Citation